Overlapping and discrete aspects of the pathology and pathogenesis of the emerging human pathogenic coronaviruses SARS‐CoV, MERS‐CoV, and 2019‐nCoV. Issue 5 (21st February 2020) - Liu, Jia; Zheng, Xin; Tong, Qiaoxia; Li, Wei; Wang, Baoju; Sutter, Kathrin; Trilling, Mirko; Lu, Mengji; Dittmer, Ulf; Yang, Dongliang
Abstract: First reported from Wuhan, The People's Republic of China, on 31 December 2019, the ongoing outbreak of a novel coronavirus (2019‐nCoV) causes great global concerns. Based on the advice of the International Health Regulations Emergency Committee and the fact that to date 24 other countries also reported cases, the WHO Director‐General declared that the outbreak of 2019‐nCoV constitutes a Public Health Emergency of International Concern on 30 January 2020. Together with the other two highly pathogenic coronaviruses, the severe acute respiratory syndrome coronavirus (SARS‐CoV) and Middle East respiratory syndrome coronavirus (MERS‐CoV), 2019‐nCov and other yet to be identified coronaviruses pose a global threat to public health. In this mini‐review, we provide a brief introduction to the pathology and pathogenesis of SARS‐CoV and MERS‐CoV and extrapolate this knowledge to the newly identified 2019‐nCoV. Highlights: The pathology of SARS‐CoV and MERS‐CoV is introduced. The pathogenesis of SARS‐CoV and MERS‐CoV is introduced. The general features of 2019‐nCoV and the disease caused by it are described.